a.
=> -3x = -18
=> x = -18 : - 3 = 6
b.
<=> (2x-1)(3-x)=0
=> x = 1/2 hoặc x =3
\(a,-3x+18=0\)
\(=-3x=-18\)
\(=x=-18:3\)
\(=6\)
\(b,3\left(2x-1\right)-x\left(2x-1\right)=0\)
\(\Rightarrow\left(2x-1\right)\left(3-x\right)=0\)
\(\Rightarrow x=\dfrac{1}{2}hoặc=3\)
\(a) -3x+18=0\)
\(<=>-3x=-18\)
\(<=>x=6\)
vậy...
\(------------\)
\(b) 3(2x-1)-x(2x-1)=0\)
\(<=>(3-x)(2x-1)=0\)
\(< =>\left[{}\begin{matrix}3-x=0\\2x-1=0\end{matrix}\right.\)
\(<=>\) \(\left[{}\begin{matrix}x=3\\x=\dfrac{1}{2}\end{matrix}\right.\)